2023
DOI: 10.1038/s42003-023-04877-0
|View full text |Cite
|
Sign up to set email alerts
|

Leaky barriers to gene sharing between locally co-existing coagulase-negative Staphylococcus species

Abstract: Coagulase-negative Staphylococcus (CoNS) are opportunistic pathogens implicated in many human and animal infections. The evolutionary history of CoNS remains obscure because of the historical lack of recognition for their clinical importance and poor taxonomic sampling. Here, we sequenced the genomes of 191 CoNS isolates representing 15 species sampled from diseased animals diagnosed in a veterinary diagnostic laboratory. We found that CoNS are important reservoirs of diverse phages, plasmids and mobilizable g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…SCCmec type VIII is most common in S. haemolyticus in our setting, however, SCCmec type VIII has only been reported in clinical S. hominis and S. epidermidis in Tunisia and Malaysia, respectively (Bouchami et al, 2011;Sani et al, 2014). Majority of SCCmec elements from methicillin resistant SOSA (57.1%) were non-typeable; this not surprising due to the high recombination rate in SOSA and partly because the current SCCmec typing scheme is dedicated to S. aureus and therefore not ideal for SOSA (Ternes et al, 2013;Ikhimiukor et al, 2023). The International Working Group on the Staphylococcal Cassette Chromosome elements 5 does not annotate SCCmec types in SOSA due to the high complexity of the elements found in SOSA.…”
Section: Discussionmentioning
confidence: 80%
“…SCCmec type VIII is most common in S. haemolyticus in our setting, however, SCCmec type VIII has only been reported in clinical S. hominis and S. epidermidis in Tunisia and Malaysia, respectively (Bouchami et al, 2011;Sani et al, 2014). Majority of SCCmec elements from methicillin resistant SOSA (57.1%) were non-typeable; this not surprising due to the high recombination rate in SOSA and partly because the current SCCmec typing scheme is dedicated to S. aureus and therefore not ideal for SOSA (Ternes et al, 2013;Ikhimiukor et al, 2023). The International Working Group on the Staphylococcal Cassette Chromosome elements 5 does not annotate SCCmec types in SOSA due to the high complexity of the elements found in SOSA.…”
Section: Discussionmentioning
confidence: 80%
“…This pattern suggests the infection history of those strains and the kind of interactions of certain E. faecium strains with their environment. This bacteriophage-mediated horizontal transfer behaviour within and between phyla plays a central role in bacterial evolution, and these interactions may trigger the transfer of certain genetic elements pertaining to pathogenicity and virulence in a specific niche, such as a hospital setting (Casjens and Hendrix 2014 ; Ikhimiukor et al 2023 ). It has been reported that certain Gram-negative-infecting viral families, such as Inoviridae , transport genes related to biofilm synthesis, immune evasion, and toxin secretion (Burckhardt et al 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…Coagulase-positive Staphylococcus (CoPS), particularly S. aureus, is a major cause of hospital-and community-acquired infections worldwide [1,2]. These infections can range from minor skin infections to severe cases such as bacteremia, endocarditis, and necrotizing pneumonia that lead to high morbidity and mortality rates [3,4].…”
Section: Introductionmentioning
confidence: 99%